Tourists’ Motivation in Focus: Contrasting Push and Pull Factors of Tuba’s Adventure Tourism - Laleo, Rachel; Dalisay, Maricar Angel; Dixon, Shanley Vanness; Bastasa, Zhyriene Shayne; Petalver, Trishia Mae; Cudapas, Sandara Jhunalyn; Rosimo, Amety Kaith; Chan, Patti Betina E. (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2025)
This study examined the motivational factors that influence participation in soft and hard adventure tourism in Tuba, Benguet. Soft adventure activities in the area include camping, swimming, and nature walks, while hard adventures involve hiking, cave exploration, and ziplining. The objective of the research was to compare the motivations of tourists and locals to provide a clearer understanding of how these factors differ and overlap. A qualitative comparative approach was used, and participants were selected through snowball sampling. Data were collected through interviews with 25 participants, composed of 16 tourists and 9 locals. Responses were analyzed using thematic analysis to identify recurring patterns and themes. Results show that soft adventure tourism is mainly motivated by low engagement and leisure, while hard adventure tourism is driven by thrill-seeking and adrenaline. Both groups, however, share motivations related to personal growth and fulfillment, balancing relaxation and challenge. Push and pull factors such as social influence, personal priorities, convenience, and accessibility also play a significant role in shaping participation. The study concluded that although soft and hard adventure activities differ in their primary motivational drivers, they also share important similarities. These findings provide useful insights for tourism development in Tuba, emphasizing the need to improve accessibility, design packages suited to different adventure levels, and promote activities that appeal to both tourists and locals.